2013
DOI: 10.24188/recia.v5.n1.2013.481
|View full text |Cite
|
Sign up to set email alerts
|

Fauna Silvestre Atropellada En Dos Vías Principales Que Rodean Los Montes De María, Sucre, Colombia

Abstract: Se registran la fauna silvestre atropellada en la carretera que comunica a Sincelejo con Ovejas y a Sincelejo con San Onofre y que bordean los Montes de María. Se recolectaron 621 especímenes atropellados durante las épocas de lluvias y sequía entre el año 2011-2012. A los especímenes colectados se les realizó la identificación hasta donde fue posible (familia, género, especie). La estacionalidad tuvo significativa influencia, la época que tuvo mayor prevalencia de atropellamientos de fauna silvestre fueron lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 6 publications
1
1
0
1
Order By: Relevance
“…In this study, road mortality was concentrated on four usually abundant, nocturnal, highly mobile, habitat generalist species: D. marsupialis, C. thous, T. mexicana, and P. cancrivorus. Our observations are consistent with findings from previous studies in Colombia, which have shown that these species of wild mammals are more prone to roadkill events (e.g., de la Ossa-Nadjar & de la Ossa-V 2013, 2015, Payan et al 2013, Castillo et al 2015, Monroy et al 2015. We hypothesize that the continued loss of reproductive-age adults of these species due to roadkill in the study area can have severe populational and ecological consequences with cumulative effects that might take multiple generations to recover, or they might never recover at all.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, road mortality was concentrated on four usually abundant, nocturnal, highly mobile, habitat generalist species: D. marsupialis, C. thous, T. mexicana, and P. cancrivorus. Our observations are consistent with findings from previous studies in Colombia, which have shown that these species of wild mammals are more prone to roadkill events (e.g., de la Ossa-Nadjar & de la Ossa-V 2013, 2015, Payan et al 2013, Castillo et al 2015, Monroy et al 2015. We hypothesize that the continued loss of reproductive-age adults of these species due to roadkill in the study area can have severe populational and ecological consequences with cumulative effects that might take multiple generations to recover, or they might never recover at all.…”
Section: Discussionsupporting
confidence: 93%
“…In Colombia, most studies investigating road impacts on wildlife populations have been focused on counts of animals killed by vehicles (e.g., de la Ossa-Nadjar & de la Ossa-V 2013, 2015, Castillo et al 2015, de la Ossa-V & Galván-Guevara 2015, Meza-Joya et al 2015, Monroy 2015, without testing spatio-temporal patterns of wildlife-vehicle collisions (but see Payan et al 2013, Ramos & Meza-Joya 2018 or landscape connectivity models to evaluate roadkill patterns. Beyond the scarce knowledge of how road mortality might affect wildlife populations, most roads in the country lack mitigation measures or they are installed intuitively without studies supporting their location and effectiveness (Payan et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…En Colombia existen diversos reportes sobre el atropellamiento de T. mexicana, siendo mencionado, inclusive, como uno de los mamíferos más atropellados en algunos tramos viales del país (Argotte & Monsalvo, 2002;Payán et al, 2013). En cuanto al Caribe colombiano, el oso melero ha sido reportado como una especie vulnerable al atropellamiento en seis de sus ocho departamentos (Sánchez-Páez et al, 2004;De la Ossa-Nadjar & De la Ossa, 2013;Payán et al, 2013;Viloria-Rivas & Chacón, 2014;De la Ossa & Galván-Guevara, 2015;Monroy et al, 2015), lo que indica que es una problemática generalizada.…”
Section: Discussionunclassified